Brachyta (Fasciobrachyta) petriccionei, a new Longhorn beetle species from Central Italy (Coleoptera: Cerambycidae) - Rapuzzi, Pierpaolo; Bologna, Marco A.; Poloni, Riccardo (Fragmenta entomologica, 2019)
In this paper we describe a new species of Cerambycidae of the Genus Brachyta, Subgenus Fasciobrachyta, close to Brachyta balcanica (Hampe, 1870). The new species, very likely associated as larvae with roots of Paeonia officinalis, was collected in the Majella National Park (Abruzzo, Italy) and its phylogenetic position clearly reveals a Transadriatic origin.